Three-channel control architecture for multilateral teleoperation under time delay - TÜMERDEM, UĞUR (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2019)
Multilateral teleoperation is an extension of bilateral/haptic teleoperation framework to multiple operators/robots and finds applications in haptic training. As in bilateral teleoperation, time delay is an important problem, and stability and transparency, which quantifies the performance of the teleoperation system, are critical in the design of multilateral control systems. This paper proposes a novel three-channel-based multilateral control architecture with damping injection to guarantee delay-independent L-2 stability and high transparency in multilateral teleoperation systems. The theoretical and computational analyses are verified with experiment results.
Keywords: Robotics; teleoperation; haptics; time delay; STABILITY; SYSTEMS; TRANSPARENCY; FRAMEWORK; DESIGN